An effective evidence‐based cleaning method for the safe reuse of intermittent urinary catheters: In vitro testing. Issue 3 (24th March 2020) - Wilks, Sandra A.; Morris, Nicola S.; Thompson, Richard; Prieto, Jacqui A.; Macaulay, Margaret; Moore, Katherine N.; Keevil, C. William; Fader, Mandy
Abstract: Aims: To determine a safe bactericidal cleaning method that does not damage urethral catheters used for intermittent catheterization. In some countries, single‐use catheters are the norm; in others, the reuse of catheters is common depending on health insurance, personal preference, or individual concerns about the environment. However, no recent study of cleaning methods has been published to provide evidence for the safe reuse of catheters. Methods: Using advanced microbiological methods, a laboratory study of eight cleaning methods was conducted. Sections of uncoated polyvinylchloride (PVC) catheters were exposed to bacterial uropathogens in physiologically correct artificial urine media then tested with a range of heat, chemical, and mechanical cleaning methods. Analysis of culturable and viable but nonculturable (VBNC) bacteria was done and direct microscopy was used. Descriptive statistics were used to compare values. Results: Heat treatments, although effective, resulted in catheter surface breakdown and damage. Ultrasonic cleaning and vinegar showed evidence of VBNC populations indicating the methods were bacteriostatic. Detergent and water wash followed by immersion in a commercially available 0.6% sodium hypochlorite solution and 16.5% sodium chloride (diluted Milton) gave consistent bactericidal results and no visible catheter damage. Conclusions: Combined mechanical and chemical treatment of a detergent and water wash followed by immersion in diluted Milton (the "Milton Method") provided consistent and effective cleaning of uncoated PVC catheters, showing bactericidal action for all uropathogens tested after repeated exposure. If found safe in clinical testing, this method could increase the reuse of catheters, reduce plastic waste in the environment, reduce cost, and increase patient choice.